News framing and media legitimacy: an exploratory study of the media coverage of the refugee crisis in the European Union (Communication & Society, 2017)
This research project focuses on a specific type of legitimacy, media legitimacy, which deals with the judgements made by the media about the legitimacy of organisations and explores the relationship between the types of frames (episodic and thematic) proposed by Iyengar (1994) and the typologies of moral legitimacy proposed by Suchman (1995): consequential, procedural, structural, and personal legitimacy. The subject of this empirical analysis will be the refugee crisis (2015-2016) in the European Union. Legitimacy rests on the consent of authority and power. Media framing can shape the opinions and political attitudes of citizens and, consequently, judgements of the legitimacy of public organisations. A content analysis was performed to measure the presence and absence of the types of legitimacy and understand the relationship with the types of episodic or thematic frames as well as the sense of appraisal using the Janis-Fadner coefficient. This research suggests that while the four types of legitimacy are present in news coverage, procedural legitimacy is more prevalent than the others, as well as more negative. This research notes the importance of process management in influencing the legitimacy of an organisation, and underlines the importance of managing the communication of public policy processes. The supporting results develop hypotheses for future research on the attribution of responsibility.